(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the author examines the phenomenon of Ukrainian historical consciousness in the conditions of polyethnical and polycultural space of modern Ukraine. The author reflects the stages of forming of ethnomental identity on the Ukrainian walks of life